Classification of X-ray sources in the direction of M31 - Vasilopoulos, G.; Hatzidimitriou, D.; Pietsch, W. (2012)
M31 is our nearest spiral galaxy, at a distance of 780 kpc. Identification of X-ray sources in nearby galaxies is important for interpreting the properties of more distant ones, mainly because we can classify nearby sources using both X-ray and optical data, while more distant ones via X-rays alone. The XMM-Newton Large Project for M31 has produced an abundant sample of about 1900 X-ray sources in the direction of M31. Most of them remain elusive, giving us little signs of their origin. Our goal is to classify these sources using criteria based on properties of already identified ones. In particular we construct candidate lists of high mass X-ray binaries, low mass X-ray binaries, X-ray binaries correlated with globular clusters and AGN based on their X-ray emission and the properties of their optical counterparts, if any. Our main methodology consists of identifying particular loci of X-ray sources on X-ray hardness ratio diagrams and the color magnitude diagrams of their optical counterparts. Finally, we examined the X-ray luminosity function of the X-ray binaries populations.